A Cluster RCT to Reduce Workers' Sitting Time: Impact on Cardiometabolic Biomarkers. Issue 10 (October 2017) - HEALY, GENEVIEVE N.; WINKLER, ELISABETH A. H.; EAKIN, ELIZABETH G.; OWEN, NEVILLE; LAMONTAGNE, ANTHONY D.; MOODIE, MARJ; DUNSTAN, DAVID W.
ABSTRACT: Purpose: To evaluate the initial and long-term impacts on cardiometabolic health indicators of the Stand Up Victoria intervention—a 12-month, multicomponent workplace-delivered intervention that successfully reduced overall sitting time, primarily by increasing standing time. Methods: Office worksites (≥1 km apart) from a single organization were cluster randomized to intervention ( n = 7) or control ( n = 7). Participants were 136 intervention and 95 control desk-based workers (5–39 per worksite; 68% women; mean ± SD age = 45.6 ± 9.4 yr). Outcomes, assessed at baseline (0 months), 3, and 12 months, were 14 individual biomarkers of body composition, blood pressure, glucose metabolism, lipid metabolism, and a composite overall cardiometabolic risk score. Intervention effects were assessed by linear mixed models, accounting for repeated measures and clustering, baseline values, and potential confounders. Missing data were multiply imputed. Significance was set at P < 0.05, two-tailed. Results: No significant intervention effects were observed at 3 months. Significant effects, favoring intervention, were observed at 12 months for fasting glucose (−0.34; 95% confidence interval [CI], −0.65 to −0.03; P = 0.028 mmol·L −1 ) and the overall cardiometabolic risk score (−0.11, 95% CI, −0.29 to −0.00; P = 0.046). Other intervention effects were typically weakly in favor of the intervention group, but were nonsignificant and estimated with wide CI. Conclusions: In "healthy" workers (not selected as having any specific health condition), a workplace intervention showed a small benefit for improving biomarkers of cardiometabolic risk, but only with 12 months of intervention and not for all biomarkers. Long-term facilitation of movement and standing at work may be a useful approach to reducing cardiovascular disease risk in the working population. The potential benefits for workers at high risk for cardiovascular disease (e.g., with diabetes) may be even greater and merit investigation. Abstract : Supplemental digital content is available in the text.